The Waqf Legal Politics in Law Reform Perspective - Ajie, Okky Prastyo; Arpangi, Arpangi (Law Development Journal, 2021)
This study aims to analyze the previous ijtihad fuqaha towards the designation of waqf land was aimed at the benefit of the people in accordance with the social conditions at that time. Likewise, the ijtihad of Indonesian scholars towards the development of waqf objects is for the benefit of mankind which is adapted to the needs and social settings at this time. Because basically the law is the articulation of human thought and activity in his life. Legislation is the main way of creating laws. Regulations is the main joint of the national legal system in Indonesia. The research method used by the author is normative juridical research. This scientific method approach is used to find the truth based on the theory of normative legal experts. In addition, legislation is a very effective instrument in law reform because of its binding and coercive legal force. Legal politics has a very important role in the formation of laws and regulations and Indonesian national law, considering that legal politics is used as a basic guide in the process of determining values, establishing and developing national law in Indonesia. Waqf as an institution derived from Islamic law plays an important role in the religious and social life of Muslims. In conclusion, the waqf legal regulations that are applied to Indonesian Muslims today can be found in book III of the Compilation of Islamic Law (KHI) and Act No. 41 of 2004 concerning Waqf.